Food waste in lower-middle income households: a qualitative analysis of antecedents and a typology of food wasters - Araújo, Gustavo Porpino de (2015)
This dissertation, based on empirical data collected with 50 nutritional gatekeepers distributed in Brazil (n=30) and the US (n=20), aims to provide an improved understanding of household food waste in the lower-middle income context. The thesis is comprised in three essays, which combined, fulfill the objectives of identifying the core antecedents of food waste and delineating a typology of food wasters. Additionally, it presents a contextualization of food waste worldwide and a concluding chapter proposes an agenda for future research studies on consumer food waste. Food waste, as a research theme, provides the opportunity for scholarly work in marketing to meet the criteria of managerial, public policy, and societal relevance. In the first article, I describe the drivers of the so-called “food waste paradox”, the identification and analysis of food waste in families with income constraints while presenting the food consumption itinerary and the core antecedents of wasted food. This first essay, based on data collected in Brazilian families, illustrates also how cultural norms, such as over-preparing food to show hospitality or as a form not to be perceived as poor, can generate more food waste. In the second essay, a grounded theory oriented research highlights the role of affection and abundance on consumer food waste. This second study presents a framework with six dimensions of food waste - 1. Affection; 2. Abundance; 3. Multiplicity of choices; 4. Convenience; 5. Procrastination; 6. Unplanned routine - to enrich the theoretical contributions. Based on empirical data collected in American families, it provides novel explanations, such as on how stockpiling comfort foods in abundance – a form of both boosting positive self-emotions and showing affection for kids – can promote more food waste. In sum, the second essay identifies a negative outcome of affection and food abundance in the family context, while providing a theoretically relevant general framework for the food waste phenomenon. Finally, the third essay, drawing from the entire dataset and a new data gathering from ten families, proposes a behavioral typology of household food waste, an original contribution to consumer behavior studies. The identification of five distinct food wasters’ types - (1) Caring mothers; (2) Heavy cooks; (3) Leftovers killers; (4) Procrastinators; (5) Resourceful mothers - contributes to theory, whilst a number of potential implications for nutritional educators and government officials are explored in light of the findings. A comparison of the Brazilian and American samples explains the characteristics of each type identified, showing many similarities in their respective food waste behaviors. Waste levels perceived per country are also compared. Overall, findings from the three studies, such as the itinerary presented and the identification of the major drivers of household food waste, can contribute to maximizing the results of campaigns aimed at mitigating food waste, and they provide insights for retailers interested in sustainability initiatives. Broadly-based, results presented can also be applied to improve hunger relief programs and nutritional education projects undertaken by the public sector or NGOs.